Influencing the Need for Multiple Peripheral Intravenous Cannulations in Adult Inpatients - Ahmed, Farhan; Arshad, Abdul Rehman; Niazi, Ghulam Abbas Khan; Dar, Abdul Rehman Azeem; Rashid, Amir; Zahid, Usama (Pakistan Armed Forces Medical Journal, 2025)
Objective: To identify factors predictive of the need for repeated peripheral intravenous cannulations in hospitalized patients.Study Design: Prospective longitudinal study.Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi, Pakistan, from Jan to Feb 2023Methodology: Adult patients hospitalized for more than two days and with peripheral intravenous cannulas were required for IV injections. Exclusion criteria included the requirement of more than one cannula simultaneously, cannulation of lower extremity veins, and unwillingness. Data on the number, site, size, dwell time, and reason for removal of cannulas were recorded.Results: There were 615 patients with a median age of 48 years (interquartile range: 32- 63 years), including 490(79.67%) males, who remained admitted for 5.87±2.17 days. A total of 1236 cannulas were inserted, accounting for 2.01±0.83 cannulas per patient, with a mean dwell time of 2.57±0.75 days. 692(55.99%) cannulas were placed on right side and 544(44.01%) on left; 616(49.17%) were passed over the forearms/ antecubital fossa and 620(50.83%) over wrists/ dorsum of hands. Single cannulation was required in 187(30.41%) patients, whereas 428(69.59%) required repeated insertions. Of the 1049 repeat cannulations, 541(51.57%), 63(6.01%), and 17(1.62%) had to be undone because of blockade, dislodgement, and thrombophlebitis, respectively. Increasing patient age (odds ratio 1.026), smaller cannula size (odds ratio 3.497), and placement of cannulas on wrist/ dorsal aspect (odds ratio 3.497) or left upper extremity (odds ratio 1.574) were associated with a subsequent need for repeat cannulation.Conclusion: The frequency of repeated intravenous cannulations may be minimized by selecting appropriately sized larger-bore cannulas.